Day surgery versus inpatient surgery: A cost comparison. - Karpman, Shelby. (University of Ottawa (Canada), 1982)
Day surgery is a rapidly growing alternative mode of treating patients. Instead of a two to three day stay in the hospital, the patient arrives the morning of surgery, is operated on and returns home the same evening. There are restrictions on the type of patient and type of procedure that can be done in day surgery. It also has been shown that day surgery is a much less costly method of treating patients, provided the patients and the procedure meet the day surgery requirements. This study was conducted at the University of Alberta Hospital in Edmonton, Alberta. It looked at six procedures that meet the day surgery requirements (Dilatation and Curettage, Laparoscopy, Non-Recurrent Inguinal Hernia, Breast Biopsy, Cataracts and Haemorrhoids) and the cost associated with each procedure both on an inpatient and day surgery basis. A sample of medical records for each procedure was examined and information concerning Nursing, Supply, Drug and Test costs, as well as, length of stay was extracted. Hotel service costs were obtained from various departments and the remaining costs, including Administration and Plant, were obtained from the Hospital's annual return to the government. The costs were added up to give a procedure cost for each procedure on an inpatient and day surgery basis. Then using data derived from the medical records, including age and complications, an eligibility rate (the percentage of patients eligible for day surgery) was derived. This was multiplied by the total number of that particular procedure performed in 1980 and was then multiplied by the procedure cost. The final result was the savings that would have possible if a greater percentage of procedures had on a day surgery basis. The results show that significant savings can be expected by substituting day for inpatient surgery, providing a number of inpatient beds are closed to correspond with the increase in day surgery.
Keywords: Health Sciences, Health Care Management.